Motivational mediation between coping and post-traumatic growth in previously bullied college students - Ravelo, Yennifer; Alegre, Olga M.; Marrero, Hipólito; Gonzalez-Mendez, Rosaura (Frontiers in Psychology, 2022)
Research has consistently shown that experiences of peer victimization may have long lasting negative consequences on health and academic achievement, less attention has been paid to the association between past bullying and post-traumatic growth in college students. This cross-sectional study aims to examine the role of different motivational orientations (The Behavioral Inhibition and Behavioral Activation Systems (BIS/BAS) and regulatory focus) as potential mediators between cognitive strategies (rumination and resilient coping) and post-traumatic growth (PTG). Using a large sample of 1,134 college students, 85 were selected who were in their first year of college and had reported having previously experienced bullying. After classifying the participants according to their the 33rd and 66th percentile scores on post-traumatic growth, a univariate analysis of variance (ANOVA) indicated significant differences between the low and high groups, with those highest in PTG showing the highest scores on drive approach, focus on promotion, and resilient coping. Conditional process analysis with these significant variables revealed that regulatory focus on promotion mediates between resilient coping and post-traumatic growth, whereas drive moderates the link between both variables. The findings shed light on the motivational mechanisms underlying PTG, which may be useful to guide interventions to prevent the consequences of bullying.